Mathematical model for postponing time in reverse logistics network design with capacity levels - Servare Junior, Marcos Wagner Jesus; Cardoso, Patrícia Alcântara (Brazilian Journal of Production Engineering, 2020)
A crucial issue in the design of efficient logistics systems is the locations for inventory. In parallel to this, the worldwide growth in the consumption of products causes the emergence of a concern about the end of the useful life or the end of the consumption of these products since their inappropriate disposal can cause serious environmental problems. The disposal of used cooking oil is one of these situations, which when improperly disposed of can have a severe environmental impact in a region. In this paper, the time postponement problem is analyzed and was proposed a mathematical modeling for the use of time postponement in the reverse supply chain design, with validation of its use with the application in the reverse logistics system of cooking oil in Vitória from scenarios to evaluate the technique and then solve efficiently e with an optimal solution the problem with the implementation in CPLEX 12.6.
Keywords: Time Postponement; Reverse logistic; Supply Chain Design; Mathematical Modeling; Used Cooking Oil